1997
DOI: 10.1161/01.cir.96.6.1722
|View full text |Cite
|
Sign up to set email alerts
|

Two- and Three-Dimensional Transesophageal Echocardiography in Patient Selection and Assessment of Atrial Septal Defect Closure by the New DAS–Angel Wings Device

Abstract: Three-dimensional imaging provides unique images and projections that were essential for understanding the spatial relationship of the device to the atrial septum. Three-dimensional echocardiography significantly enhanced our understanding of two-dimensional images and provided an imaging conceptualization that should aid in future development of device closures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 5 publications
2
66
1
5
Order By: Relevance
“…Two-dimensional echocardiography can cut the defect in different planes but does not reflect its true shape. Three-dimensional echocardiography mimics the atriotomy view on a beating heart and allows the atrial septal defect to be described through the cardiac cycle [13,15] . One of our most striking findings was the great variability of the shape of the atrial septal defects.…”
Section: Atrial Septal Defect Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional echocardiography can cut the defect in different planes but does not reflect its true shape. Three-dimensional echocardiography mimics the atriotomy view on a beating heart and allows the atrial septal defect to be described through the cardiac cycle [13,15] . One of our most striking findings was the great variability of the shape of the atrial septal defects.…”
Section: Atrial Septal Defect Anatomymentioning
confidence: 99%
“…New information by means of the cardiac cycle with three-dimensional echocardiography, regarding the shape of the defect and the surface area have recently been reported [14] . Three-dimensional echocardiography may help to assess the position of the device after its deployment [15] . We report our experience of threedimensional echocardiography for: (1) patient selection according to the atrial septal defect anatomy and (2) early assessment of transcatheter atrial septal defect closure by the Cardioseal device.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, that blind technique makes changes in dynamic geometry and in the thin surrounding rims of the ASD. There were some reports that three dimensional TEE providing en face view of ASD could be used instead of balloon sizing for the selection of ASO size [19,20]. Also, Zanchetta et al used intracardiac echocardiography as a new efficient device selection method instead of balloon sizing [21].…”
Section: российский кардиологический журнал № 3 (101) | 2013mentioning
confidence: 99%
“…19,30 For instance, ASD maximal diameter appears to be more accurately measured by 3-dimensional TEE than 2-dimensional TEE compared with intraoperative measurements 31 or balloon sizing. 32 Additionally, several groups 20,33,34 have reported that 3-dimensional TEE is superior to 2-dimensional TEE in consistently detecting the features of complex secundum defects (eccentrically shaped, multiple, atypical location, etc). Given that even after screening with 2D TEE 10% of patients have an attempted but ultimately unsuccessful transcatheter closure, 35 the implication is that clinical management would be improved by the use of 3-dimensional imaging.…”
Section: Thomson Et Al Direct En Face Imaging Of Atrial Septal Defectmentioning
confidence: 99%
“…The inferoposterior portion of the interatrial septum is poorly visualized as a result of artifactual dropout; small fenestrations may be missed because of inadequate spatial resolution; and depending on patient compliance, movement can result in image misalignment and reconstruction artifacts. 32,33,36 On the other hand, CMR also has some limitations. In the present study, ASD was ruled out correctly by en face veCMR in the 5 patients with PFO; however, in only 3 patients was the PFO detected by CMR (first-pass perfusion imaging).…”
Section: Thomson Et Al Direct En Face Imaging Of Atrial Septal Defectmentioning
confidence: 99%